PRINTED BIBLIOGRAPHIC INFORMATION RESOURCES IN LITHUANIA IN 2001–2005 - JANONIS, OSVALDAS (Knygotyra, 2015)
Recently, because of the progress in digital bibliographic information resources and bibliographic databases and for other reasons, many changes have appeared in the field of the system of bibliographic information. To identify the new trends of this field is only possible through continuous monitoring. The object of this article is the bibliography of printed publications of various kinds and types, bibliographic index lists and reviews for the period 2001–2005. Changes of periodicals and retrospective bibliography publications are analysed in the article. Results of this analysis may be useful not only for bibliography researchers and teachers of bibliographic disciplines, but also for managers of the bibliographic process, promoters of bibliographic recommendations and bibliographers themselves.
Keywords: ...